Metabolism of 2-chlorobenzoic acid in Pseudomonas stutzeri - Kozlovsky, S A; Kunc, F (Folia microbiologica, 1995)
3-Chloropyrocatechol is formed as a result of oxidation of 2-chlorobenzoate by Pseudomonas stutzeri. 2-Chloro-cis,cis-muconic acid is the product of oxidation of 3-chloropyrocatechol. A catabolic pathway for the degradation of 2-chlorobenzoate by a newly isolated strain of P. stutzeri is proposed.
Keywords: biodegradace; Polychlorinated Biphenyls; Pseudomonas; katecholy; dioxygenasy; bakteriální proteiny; polychlorované bifenyly; Bacterial Proteins; Oxygenases; Catechols; kyselina sorbová; oxygenasy; Catechol 1,2-Dioxygenase; Dioxygenases; Chlorobenzoates; oxidace-redukce; aerobióza; Pesticide Residues; adipáty; Oxidation-Reduction; Environmental Pollutants; rezidua pesticidů; katechol-1,2-dioxygenasa; Aerobiosis; Biodegradation, Environmental; chlorbenzoáty; Sorbic Acid; látky znečišťující životní prostředí; Adipates